Patients' perceptions on the importance of pre-operative visit carried out by perioperative nurse for patients going for surgery - Katherine Baha @ Khatijah, Abdullah (Faculty of Medicine & Health Sciences, 2008)
The present study was undertaken to assess the importance of pre-operative visits carry out by perioperative nurse through patients' perception